2009
DOI: 10.2118/09-02-47
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concentration-Dependence of Diffusion Coefficient on VAPEX Drainage Rates

Abstract: The VAPEX analytical model is extended to cover situations when diffusion coefficients are dependent on concentration due to the extreme viscosity reduction with solvent dissolution into bitumen. The new analytical model covers such situations along with the cases in which the diffusion coefficient and viscosity relate to each other under the Stokes-Einstein law. In the process, a new concept of the 'average flow fraction of bitumen' in the flowing mixtures is introduced. The modelled result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…The value of n used in all coinjection cases in this research is 0.25. The resulting distribution shape is in agreement with the experimental observations by Okazawa [41] and Oballa and Butler [42] and the numerical simulation results in this research and Keshavarz et al [23]. In Eq.…”
Section: Approximate Distributions Of Temperature and Solvent Beyond supporting
confidence: 92%
See 1 more Smart Citation
“…The value of n used in all coinjection cases in this research is 0.25. The resulting distribution shape is in agreement with the experimental observations by Okazawa [41] and Oballa and Butler [42] and the numerical simulation results in this research and Keshavarz et al [23]. In Eq.…”
Section: Approximate Distributions Of Temperature and Solvent Beyond supporting
confidence: 92%
“…However, the diffusion flux is considered to be inversely proportional to viscosity or viscosity to some power, and proportional to temperature or temperature to some power [24]. As a result, concentration profiles in diffusion experiments exhibited abrupt front-end profiles in Okazawa [41] and Oballa and Butler [42].…”
Section: Approximate Distributions Of Temperature and Solvent Beyond mentioning
confidence: 99%
“…Okazawa [15] investigated the effects of concentration-dependent diffusion coefficient on VAPEX drainage rates and concluded that the base functionalities of bitumen rates to other key parameters remain unchanged with diffusion coefficient. Hence, the assumption of constant diffusion coefficient D s is generally considered reasonable.…”
Section: Formulation For the Original Hele-shaw Modelmentioning
confidence: 99%
“…Okazawa [21] investigated the effects of concentration-dependence of diffusion coefficient on Vapex drainage rates and concluded that the base functionalities of bitu men rates to other key parameters remain unchanged with a concentration-dependent Ds. Okazawa [21] investigated the effects of concentration-dependence of diffusion coefficient on Vapex drainage rates and concluded that the base functionalities of bitu men rates to other key parameters remain unchanged with a concentration-dependent Ds.…”
Section: Formulation For a Porous Mediummentioning
confidence: 99%